2021
DOI: 10.2147/eb.s300454
|View full text |Cite
|
Sign up to set email alerts
|

Monocular and Binocular Visual Function Deficits in Amblyopic Patients with and without Fusion Maldevelopment Nystagmus

Abstract: Purpose The aim of the study is to examine the association between amblyopia type and the presence of nystagmus on binocular and monocular functions of the fellow (FE) and amblyopic eye (AE). Methods We recruited 19 controls and 44 amblyopes (anisometropes=13, strabismic=10, mixed=21). We measured visual, grating, and vernier acuities and high/low spatial frequency (SF) contrast sensitivities in each eye using a staircase method. Stereoacuity was measured with the Titmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“… 40 , 47 , 93 We have shown that patients with FMN had worse stereopsis deficits than patients without FMN. 70 In the current study, most of the patients with FMN had absent stereopsis. We examined the inter-ocular suppression using dichoptic motion coherence, and preliminary analysis demonstrates that patients with FMN had greater inter-ocular suppression for a given level of visual acuity deficits.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“… 40 , 47 , 93 We have shown that patients with FMN had worse stereopsis deficits than patients without FMN. 70 In the current study, most of the patients with FMN had absent stereopsis. We examined the inter-ocular suppression using dichoptic motion coherence, and preliminary analysis demonstrates that patients with FMN had greater inter-ocular suppression for a given level of visual acuity deficits.…”
Section: Discussionmentioning
confidence: 48%
“… 52 We have also found that patients with amblyopia with nystagmus have greater impairment of visual functions with increased amplitude of quick phase, eye position variance, and velocities of the slow phases compared to patients without nystagmus. 52 , 65 , 87 These collectively suggest that increased fixation instability with increased amplitude and velocities of fast and slow FEMs in amblyopia are associated with worse visual function deficits.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent paper from our lab, we have systematically evaluated stereopsis in patients with and without nystagmus as a function of severity of amblyopia. We found that mild to moderate amblyopic patients with nystagmus were more likely to have absent stereopsis compared to patients without nystagmus 34 . We have also previously reported that amblyopic patients with microstrabismus and nystagmus were more likely to have poor recovery of stereopsis and require longer duration of amblyopia treatment despite improvement in visual acuity with patching treatment 19 , 23 , 35 .…”
Section: Discussionmentioning
confidence: 59%
“…ET and VOG are currently used in various areas associated with visual functioning, including nystagmus, 6–8 oculomotricity, 9–14 contrast sensitivity, 15 visual acuity, 15 pupillography, 16 cyclotorsion, 17,18 and primarily for detecting and/or quantifying ocular misalignment, whether it be heterophoria 19–24 or heterotropia 25–52 …”
Section: Introductionmentioning
confidence: 99%